Medication Adherence in Children with Asthma - McCrossan P; Shields MD; McElnay JC (Patient Preference and Adherence, 2024)
Paddy McCrossan,1 Michael D Shields,2 James C McElnay3 1Paediatric Respiratory Medicine, Royal Belfast Hospital for Sick Children, Belfast, Northern Ireland; 2Wellcome-Wolfson Institute for Experimental Medicine, Queen’s University Belfast, Belfast, Northern Ireland; 3School of Pharmacy, Queen’s University Belfast, Belfast, Northern IrelandCorrespondence: James C McElnay, Email j.mcelnay@qub.ac.ukAbstract: Asthma is the most common chronic disease in childhood. If untreated, asthma can lead to debilitating daily symptoms which affect quality of life, but more importantly can lead to fatal asthma attacks which unfortunately still occur globally. The most effective treatment strategy for controlling asthma is for the patient to follow a personalised asthma action plan (PAAP) which will invariably include regular use of an inhaled corticosteroid. To examine medication adherence in children with asthma, we collated recent evidence from systematic reviews in this area to address the following 5 key questions; What is adherence? Is there evidence that children are not adhering to preventer medication? Why is adherence poor and what are the barriers to adherence? Does good adherence improve outcomes in asthma? And lastly, how can treatment adherence be improved?Keywords: asthma, adherence, inhaler, inhaled corticosteroid, children